The Pilot Creation of Sustainable Stall Design to Promote Temporary Pottery Market in the Baan Muang Kung Community - Lueakha, Jureepon; Tongngam, Pataravadee (International Journal of Building, Urban, Interior and Landscape Technology, 2024)
Although local intellectual property products have received support from both the government and private sectors, including increasing consumer interest in craft products, the residents of the Muang Kung community, Chiang Mai province, who produce handmade clay pottery with unique and distinctive shaping techniques and intricate patterns, still lack a market space to accommodate their products. Therefore, it is necessary to study the sustainable market format to help promote community products appropriately and stimulate tourism in this area. This research aims to achieve the following objectives (1) Study sustainable market pattern design principles suitable for community markets (2) Explore the potential capabilities and the local community’s requirements in market (3) Propose sustainable market design guideline to promote community products. This research primarily explores the sustainability value of a sustainable market within the field of retail design, employing qualitative research methods such as interviews, observational note-taking, photography, and comparative case study analysis. The on-site survey to determine the project’s feasibility involved convening a community meeting with 50 residents to discuss findings. The outcomes of this gathering were then used in designing the temporary market. The findings present design guidelines that illustrate how markets continue to play important socio-economic roles in local communities, serving as key components that can be transformed to promote sustainable development. The proposed design practice guidelines encompass considerations such as site layout, the application of sustainable design principles, including the thoughtful selection of sustainable materials, the incorporation of flexible design, and the creation of participatory area experiences to attract people.